Imatinib therapy for patients with recent-onset type 1 diabetes: a multicentre, randomised, double-blind, placebo-controlled, phase 2 trial. Issue 8 (August 2021) - Gitelman, Stephen E; Bundy, Brian N; Ferrannini, Ele; Lim, Noha; Blanchfield, J Lori; DiMeglio, Linda A; Felner, Eric I; Gaglia, Jason L; Gottlieb, Peter A; Long, S Alice; Mari, Andrea; Mirmira, Raghavendra G; et al.
Summary: Background: Type 1 diabetes results from autoimmune-mediated destruction of β cells. The tyrosine kinase inhibitor imatinib might affect relevant immunological and metabolic pathways, and preclinical studies show that it reverses and prevents diabetes. Our aim was to evaluate the safety and efficacy of imatinib in preserving β-cell function in patients with recent-onset type 1 diabetes. Methods: We did a multicentre, randomised, double-blind, placebo-controlled, phase 2 trial. Patients with recent-onset type 1 diabetes (<100 days from diagnosis), aged 18–45 years, positive for at least one type of diabetes-associated autoantibody, and with a peak stimulated C-peptide of greater than 0·2 nmol L −1 on a mixed meal tolerance test (MMTT) were enrolled from nine medical centres in the USA (n=8) and Australia (n=1). Participants were randomly assigned (2:1) to receive either 400 mg imatinib mesylate (4 × 100 mg film-coated tablets per day) or matching placebo for 26 weeks via a computer-generated blocked randomisation scheme stratified by centre. Treatment assignments were masked for all participants and study personnel except pharmacists at each clinical site. The primary endpoint was the difference in the area under the curve (AUC) mean for C-peptide response in the first 2 h of an MMTT at 12 months in the imatinib group versus the placebo group, with use of an ANCOVA model adjusting for sex, baseline age, and baseline C-peptide, with further observation up to 24 months. The primary analysis was by intention to treat (ITT). Safety was assessed in all randomly assigned participants. This study is registered with ClinicalTrials.gov, NCT01781975 (completed). Findings: Patients were screened and enrolled between Feb 12, 2014, and May 19, 2016. 45 patients were assigned to receive imatinib and 22 to receive placebo. After withdrawals, 43 participants in the imatinib group and 21 in the placebo group were included in the primary ITT analysis at 12 months. The study met its primary endpoint: the adjusted mean difference in 2-h C-peptide AUC at 12 months for imatinib versus placebo treatment was 0·095 (90% CI −0·003 to 0·191; p=0·048, one-tailed test). This effect was not sustained out to 24 months. During the 24-month follow-up, 32 (71%) of 45 participants who received imatinib had a grade 2 severity or worse adverse event, compared with 13 (59%) of 22 participants who received placebo. The most common adverse events (grade 2 severity or worse) that differed between the groups were gastrointestinal issues (six [13%] participants in the imatinib group, primarily nausea, and none in the placebo group) and additional laboratory investigations (ten [22%] participants in the imatinib group and two [9%] in the placebo group). Per the trial protocol, 17 (38%) participants in the imatinib group required a temporary modification in drug dosing and six (13%) permanently discontinued imatinib due to adverse events; five (23%) participants in the placebo group had temporary modifications in dosing and none had a permanent discontinuation due to adverse events. Interpretation: A 26-week course of imatinib preserved β-cell function at 12 months in adults with recent-onset type 1 diabetes. Imatinib might offer a novel means to alter the course of type 1 diabetes. Future considerations are defining ideal dose and duration of therapy, safety and efficacy in children, combination use with a complimentary drug, and ability of imatinib to delay or prevent progression to diabetes in an at-risk population; however, careful monitoring for possible toxicities is required. Funding: Juvenile Research Diabetes Foundation.